DOI: 10.11606/t.11.2009.tde-19052009-085313
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial e temporal, inimigos naturais e tabela de vida ecológica de Diaphorina citri Kuwayama (Hemiptera: Psyllidae) em citros em São Paulo

Abstract: Spatial and seasonal distribution, natural enemies and ecological life table of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) in citrus groves in São Paulo Huanglongbing (HLB), or citrus greening disease, has been considered the worst and most destructive disease that occurs in all citrus varieties in the world. Until today, effective control measures are unknown. However, three main measures have been recommended that may reduce the spread of the disease: (1) propagation of healthy plants; (2) elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
15

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
0
2
0
15
Order By: Relevance
“…Deforestation for agriculture and the predominant citrus culture on farms surrounding the state have probably influenced the capture as well as the colonization of sylvatic triatomines in the experimental sentinel sites, because the orange plantations harbor a large number of pests (Yamamoto et al, 2001), such as Diaphorina citri, a Hemiptera, Psyllidae, vector of "greening" or "huanglongbing" (Silva et al, 2009), with a wide geographic distribution, found in citrus crops in the State of São Paulo (Paiva, 2009). This insect occurs mainly in new shoots (Yamamoto et al, 2001), such as those of the crops from the farm next to the site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deforestation for agriculture and the predominant citrus culture on farms surrounding the state have probably influenced the capture as well as the colonization of sylvatic triatomines in the experimental sentinel sites, because the orange plantations harbor a large number of pests (Yamamoto et al, 2001), such as Diaphorina citri, a Hemiptera, Psyllidae, vector of "greening" or "huanglongbing" (Silva et al, 2009), with a wide geographic distribution, found in citrus crops in the State of São Paulo (Paiva, 2009). This insect occurs mainly in new shoots (Yamamoto et al, 2001), such as those of the crops from the farm next to the site.…”
Section: Discussionmentioning
confidence: 99%
“…This insect occurs mainly in new shoots (Yamamoto et al, 2001), such as those of the crops from the farm next to the site. To prevent their colonization and prevent them from spreading to other farms, the citrus growers perform aerial sprayings with deltamethrin and thimetoxam insecticides (Paiva, 2009) Although chemical control of the environment is not so effective due to climate changes that hinder its residual effect (Dias, 2001), the periodic fumigations made by the farmers in current citrus plantations possibly interfered with the colonization of wild triatomines.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente a principal praga de citrosé a Diaphorina citri (Hemiptera: Psyllidae), que transmite a bactéria Candidatus Liberibacter americanus, causadora do "greening" -doença atualmente presente em 18, 57% dos talhões do parque citrícola de SP [5].…”
Section: Introductionunclassified
“…No Município de Inconfidentes, foram identificadas quatro propriedades comerciais de citros segundo os registros fornecidos pelo IMA. O Município, detém uma INTRODUÇÃO O aparecimento de pragas e doenças na citricultura não é uma novidade, mas atualmente a produção dos citros vem sendo fortemente ameaçada pelo Huanglongbing, (HLB), uma doença muito agressiva e destrutiva, causada por bactérias do gênero Liberibacter spp (Paiva, 2009), cujo o vetor é a Diaphorina citri, Hemiptera: Liviidae (Burckhardt & Ouvrard, 2012).…”
unclassified